Human Resource Management Strategies to Foster Organizational Innovation through an Innovation-Based HR Approach - Abdus Salam; Syamsul Rizal; Imilda Imilda (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This research investigates the influence of human resource management strategies on organizational innovation through an innovation-focused HR approach within service, technology, trade, and creative sectors in Indonesia. Utilizing a quantitative methodology, the study involved convenience sampling to gather data from 150 participants, including operational staff, supervisors, and managers. A five-point Likert scale questionnaire facilitated data collection. Analysis was conducted using SPSS version 25 and SmartPLS 4, encompassing validity and reliability assessments, as well as evaluations of both outer and inner models, alongside bootstrapping techniques. Findings reveal a positive and significant relationship between human resource management strategies and the innovation-focused HR approach, indicated by a coefficient of 0.692 and a p-value of 0.000. Furthermore, the innovation-focused HR approach positively impacts organizational innovation, demonstrated by a coefficient of 0.486 and a p-value of 0.001. Additionally, human resource management strategies directly influence organizational innovation with a coefficient of 0.327 and a p-value of 0.003. The results underscore the role of job training, competency development, leadership support, employee engagement, and a collaborative work environment in enhancing the organization’s capacity to innovate services, refine operational processes, and bolster competitive advantage.